Consonant Changes in Korean Singers Pronunciation - Sendy Intania Hermastuti; Arina Isti'anah (Journal of Language and Literature, 2018)
Music industry in Indonesia is now filled with many genres or types of music. One of them that is very famous nowadays is a music genre called K-pop or Korean pop, originating from South Korea. In line with the development of K-pop music that continues worldwide, Korean singers start making English songs. There were two objectives to be discussed in this article: to find out the consonants that are usually changed or replaced by Korean singers and find the phonological patterns found in the consonant changes. Phonological approach was conducted by involving purposive sampling technique to collect the data. Songs by Wonder Girls, Super Junior, Bigbang, and CN Blue were analyzed in terms of the consonant changes that occurred in Korean singers pronunciation. The analysis showed that there were 7 English consonants that underwent changes in Korean singers pronunciation. Fricatives are found as the consonants that usually undergo a change. Furthermore, the phonological processes that were usually found in those consonant changes were the process of changing fricatives into stops or affricate consonants, process of changing [r] into [l], and the last is the process of palatalization.Keywords: consonant change, Korean, phonology